The postbiotic potential of Aspergillus oryzae – a narrative review - Seidler, Yvonne; Rimbach, Gerald; Lüersen, Kai; Vinderola, Gabriel; Ipharraguerre, Ignacio R. (Frontiers in Microbiology, 2024)
The filamentous fungus Aspergillus oryzae has a long tradition in East Asian food processing. It is therefore not surprising that in recent years fermentation products of A. oryzae have attracted attention in the emerging field of postbiotics. This review aims to provide a comprehensive summary of the potential postbiotic effects of fermentation products from A. oryzae, by discussing possible mechanisms of action against the background of the molecular composition determined so far. In particular, cell wall constituents, enzymes, extracellular polymeric substances, and various metabolites found in A. oryzae fermentation preparations are described in detail. With reference to the generally assumed key targets of postbiotics, their putative beneficial bioactivities in modulating the microbiota, improving epithelial barrier function, influencing immune responses, metabolic reactions and signaling through the nervous system are assessed. Drawing on existing literature and case studies, we highlight A. oryzae as a promising source of postbiotics, particularly in the context of animal health and nutrition. Challenges and opportunities in quality control are also addressed, with a focus on the necessity for standardized methods to fully harness the potential of fungal-based postbiotics. Overall, this article sheds light on the emerging field of A. oryzae -derived postbiotics and emphasizes the need for further research to fully realize their therapeutic potential.